Insurgent Marcos : The Political-Philosophical Formation of the Zapatista Subcommander - Henck, Nick, 1971- (Book collections on Project MUSE., 2016)
For over two decades now Subcommander Marcos has acted as military leader and spokesperson of Mexico's Zapatista movement. In the process of doing so he has also become a key figure in the anti-capitalist and anti-globalization movements. There has been little attempt however to examine in significant detail the political-philosophical influences at work upon this important contemporary thinker. The present study aims to rectify this by establishing which political-philosophical currents Marcos was exposed to during his formative years as a student at the National Autonomous University of Mexico, and then examining the Subcommander's discourse in order to ascertain the extent to which these persisted in his thinking years later. Concretely, what we discover is that in his youth Marcos was especially influenced by his reading of Louis Althusser, Michel Foucault, and Nicos Poulantzas, and that certain core components of their thinking helped to form, and indeed continued to inform, the Subcommander's political philosophy.